Response Time Analysis of Slotted WiDOM in Noisy Wireless Channels - Vahabi, Maryam (2015)
International Conference on Emerging Technologies and Factory Automation (ETFA 2015), Industrial Communication Technologies and Systems, Luxembourg, Luxembourg.